Haematological profile and genetic variation of brown Caucasian dairy cattle in different ecological and geographical zones - A. A. Ozdemirov; L. N. Chizhova; A. A. Khozhokov; E. S. Surzhikova; A. K. Mikhaylenko (Юг России: экология, развитие, 2022)
Aim. The rational use of North Caucasus forage lands, a large part of which is located in the mountains, is one of the important tasks in addressing the issue of improving the efficiency of cattle breeding. This appears quite challenging, as the mechanisms of adaptation of farm animals, in particular cattle, to the environmental and climatic peculiarities of a certain region have not been sufficiently explored. Since hematopoietic function of blood is the basis of organism’s vital functions and genetic polymorphism is the measure of its adaptability, the present study is aimed at examining haematological profile and the degree of genetic variation in the Brown Caucasian cattle.Materials and Methods. Haematological, genetic and statistical methods of analysis were used to examine the haematological profile and genetic structure of genes GH, PIT‐1, PRL in Brown Caucasian dairy cattle, bred in different ecological and climatic zones of Dagestan.Conclusion. This was the first time that hematopoietic function was studied in the context of genetic variation in Brown Caucasian dairy cattle bred in the foothills (100‐200 m above sea level) and mountains (650‐1,250 m above sea level). The information obtained gives an idea of and an answer to the question about the role of haematological profile and the degree of genetic variation in the development of adaptive and compensatory mechanisms to specific environmental conditions. The use of haematological, molecular and genetic methods allows the further exploration of the adaptation traits of Brown Caucasian dairy cattle for their further improvement.